Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan pada Graha Air Minum Isi Ulang Tirta Segah Trenggalek Melalui Kepuasan Pelanggan - Tony Prastyo Budi; Lativa Hartiningtyas (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In order to boost customer satisfaction and loyalty, Indonesia's free market forces business owners to raise prices and service quality. At Graha Air Refill Tirta Segah Trenggalek, This study uses customer satisfaction as an intervention to determine the relationship between price, service quality, and customer loyalty. This study, which took a quantitative approach, utilized associative research. The people who bought Graha Water Refill Tirta Segah Trenggalek were the people in this study, and 100 samples were taken from them. The sampling was done using purposeful sampling, and the research time was from Agust to September 2022. For data collection, a Google Form-based online questionnaire was utilized. According to the findings of this study, price has a positive and significant impact on customer loyalty, service quality has a positive and significant impact on customer satisfaction, and service quality does not have a significant impact on customer loyalty. Price also has a positive and significant impact on customer loyalty, customer satisfaction has a positive and significant impact on customer loyalty, and service quality does not have a significant impact on customer loyalty. cost through client steadfastness and customer loyalty at Graha Air Top off Tirta Segah Trenggalek. Keywords: Price; quality of service; customer satisfaction; and repeat business